Actin-dependent α-catenin oligomerization contributes to adherens junction assembly - Regina B. Troyanovsky; Indrajyoti Indra; Sergey M. Troyanovsky (Nature Communications)
Abstract Classic cadherins, specifically E-cadherin in most epithelial cells, are transmembrane adhesion receptors, whose intracellular region interacts with proteins, termed catenins, forming the cadherin-catenin complex (CCC). The cadherin ectodomain generates 2D adhesive clusters (E-clusters) through cooperative trans and cis interactions, while catenins anchor the E-clusters to the actin cytoskeleton. How these two types of interactions are coordinated in the formation of specialized cell-cell adhesions, adherens junctions (AJ), remains unclear. Here, we focus on the role of the actin-binding domain of α-catenin (αABD) by showing that the interaction of the αABD with actin generates actin-bound linear CCC oligomers (CCC/actin strands) incorporating up to six CCCs. This actin-driven CCC oligomerization, which is cadherin ectodomain independent, preferentially occurs along the actin cortex enriched with key basolateral proteins, myosin-1c, scribble, and DLG1. In cell-cell contacts, the CCC/actin strands integrate with the E-clusters giving rise to the composite oligomers, E/actin clusters. Targeted inactivation of strand formation by point mutations emphasizes the importance of this oligomerization process for blocking intercellular protrusive membrane activity and for coupling AJs with the actomyosin-derived tensional forces.